Research Areas on Transition to Renewable Energy Sources in Bibliographic Publications - Mammadov Nurmammad; Akbarova Samira (BIO Web of Conferences)
Energy transition involves the use of renewable energy sources to replace fossil and nuclear fuels. Energy transition issues are in the spotlight of both the global community and Azerbaijan, where the significant potential of renewable energy sources has served as the basis for integrating renewable energy into the country's energy supply system. The article provides a bibliometric analysis of current research issues on the technological aspects of energy transition using metadata of publications indexed in the Web of Science Core Collection abstract database over the past 4 years using the VOSviewer program. Three main areas of scientific research were identified: the impact of renewable energy sources on sustainable development and optimization of energy consumption; technological innovations; and environmental benefits of energy transition. The results indicate significant interest in optimizing the production, use, and utilization of energy resources, prospects for the development of renewable energy, and ensuring environmental sustainability. The results can serve as a basis for developing effective government strategies for energy transition. This study emphasizes the importance of the transition to sustainable energy sources in the context of combating climate change and ensuring environmental sustainability. The results, based on the analysis of modern trends and practices, can serve as a basis for developing effective government strategies and programs aimed at achieving sustainable development and reducing the negative impact on the environment in the energy sector.